Transcriptome-Wide Analysis of Botrytis elliptica Responsive microRNAs and Their Targets in Lilium Regale Wilson by High-Throughput Sequencing and Degradome Analysis - Gao, Xue; Cui, Qi; Cao, Qin-Zheng; Liu, Qiang; He, Heng-Bin; Zhang, Dong-Mei; Jia, Gui-Xia (Frontiers in Plant Science, 2017)
MicroRNAs, as master regulators of gene expression, have been widely identified and play crucial roles in plant-pathogen interactions. A fatal pathogen, Botrytis elliptica, causes the serious folia disease of lily, which reduces production because of the high susceptibility of most cultivated species. However, the miRNAs related to Botrytis infection of lily, and the miRNA-mediated gene regulatory networks providing resistance to B. elliptica in lily remain largely unexplored. To systematically dissect B. elliptica-responsive miRNAs and their target genes, three small RNA libraries were constructed from the leaves of Lilium regale, a promising Chinese wild Lilium species, which had been subjected to mock B. elliptica treatment or B. elliptica infection for 6 h and 24 h. By high-throughput sequencing, 71 known miRNAs belonging to 47 conserved families and 24 novel miRNA were identified, of which 18 miRNAs were downreguleted and 13 were upregulated in response to B. elliptica. Moreover, based on the lily mRNA transcriptome, 22 targets for 9 known and 1 novel miRNAs were identified by the degradome sequencing approach. Most target genes for elliptica-responsive miRNAs were involved in metabolic processes, few encoding different transcription factors, including ELONGATION FACTOR 1 ALPHA (EF1a) and TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR 2 (TCP2). Furthermore, the expression patterns of a set of elliptica-responsive miRNAs and their targets were validated by quantitative real-time PCR. This study represents the first transcriptome-based analysis of miRNAs responsive to B. elliptica and their targets in lily. The results reveal the possible regulatory roles of miRNAs and their targets in B. elliptica interaction, which will extend our understanding of the mechanisms of this disease in lily.